Design of binary polymer brushes with tuneable functionality. Issue 35 (22nd August 2018) - Bos, Inge; Merlitz, Holger; Rosenthal, Alice; Uhlmann, Petra; Sommer, Jens-Uwe
Abstract : Using coarse grained molecular dynamics simulations, we study how functionalized binary brushes may be used to create surfaces whose functionality can be tuned. Abstract : Using coarse grained molecular dynamics simulations, we study how functionalized binary brushes may be used to create surfaces whose functionality can be tuned. Our model brushes consist of a mixture of nonresponsive polymers with functionalized responsive polymers. The functional groups switch from an exposed to a hidden state when the conformations of the responsive polymers change from extended to collapsed. We investigate quantitatively which sets of brush parameters result in optimal switching in functionality, by analyzing to which extent the brush conformation allows an external object to interact with the functional groups. It is demonstrated that brushes with species of comparable polymer lengths, or with longer responsive polymers than nonresponsive polymers, can show significant differences in their functionality. In the latter case, either the fraction of responsive polymers or the total grafting density has to be reduced. Among these possibilities, a reduction of the fraction of responsive polymers is shown to be most effective.